(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This paper presents the results of a study of the accuracy of fixing body details on a flat surface and two elastic grip pawls. The obtained experimental results, concerning the displacement of a detail in longitudinal and transverse direction, have been compared with the analytically obtained errors, resulting from positioning a detail on both a cylindrical and a sheared grip pawl. It has been found that the results for the accuracy of details positioning in devices with elastic grip pawls are better than those, related to using a sheared grip pawl and a cylindrical one.